2006
DOI: 10.1016/j.jpaa.2005.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A rigidity theorem for pre-Lie algebras

Abstract: In this paper we prove a "Leray theorem" for pre-Lie algebras. We define a notion of "Hopf" pre-Lie algebra: it is a pre-Lie algebra together with a non-associative permutative coproduct ∆ and a compatibility relation between the pre-Lie product and the coproduct ∆. A non-associative permutative algebra is a vector space together with a product satisfying the relation (ab)c = (ac)b. A non-associative permutative coalgebra is the dual notion. We prove that any connected "Hopf" pre-Lie algebra is a free pre-Lie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 16 publications
(27 reference statements)
1
78
0
2
Order By: Relevance
“…This implies that every connected bidendriform bialgebra is freely generated by its primitive elements, so is isomorphic to a H D for a well chosen D (Theorem 39). A similar result is proved in [13] for preLie algebras.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…This implies that every connected bidendriform bialgebra is freely generated by its primitive elements, so is isomorphic to a H D for a well chosen D (Theorem 39). A similar result is proved in [13] for preLie algebras.…”
supporting
confidence: 77%
“…So we already have (4)-(6), and (12) + (13), (14) + (15). It is then enough to prove (13). We have: Remark.…”
Section: Bidendriform Structure On Fqsymmentioning
confidence: 96%
“…NAP -algebras. The operation * used as an auxiliary operation in the proof of the main theorem satisfies the following relation: (x * y) * z = (x * z) * y for any labelled trees x, y, z. Algebras with one binary operation satisfying this identity have already occurred in the literature in the work of M. Livernet [4], and were called NAP -algebras (for NonAssociative Perm). She showed that the labelled trees do describe the associated operad and that the product is precisely given by the operation * on trees described in the proof of Theorem 3.1.…”
Section: Comparison With Associative Jordan and Nap-algebrasmentioning
confidence: 99%
“…The aim of the present text is to prove that r is a free pre-Lie algebra. We use for this the notion of non-associative permutative algebra [14] and a manipulation of formal series. More precisely, we introduce in the second section of this text a nonassociative permutative product on r , and we show that r is free.…”
Section: Introductionmentioning
confidence: 99%